Short-term and Divergent Regulation of FGF-19 and FGF-21 during Oral Lipid Tolerance Test but not Oral Glucose Tolerance Test - Schmid, A.; Leszczak, S.; Ober, I.; Karrasch, T.; Schäffler, A. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Context: Regulation of FGF-19 and FGF-21 by oral uptake of lipids and carbohydrates in healthy individuals is poorly characterized.Objective: We investigated the regulation of FGF-19 and FGF-21 in 2 large cohorts of healthy volunteers during oral lipid tolerance test (OLTT; n=100) and oral glucose tolerance test (OGTT; n=100).Design and setting: 100 volunteers underwent OLTT and OGTT in an outpatient setting. Venous blood was drawn at 0 h (fasting) and at 2, 4, and 6 h in OLTT or 1 and 2 h in OGTT. In order to dissect carbohydrate-induced from lipid-induced effects, a special OLTT solution was applied. Subjects were characterized by anthropometric and laboratory parameters. Serum concentrations of FGF-19 and FGF-21 were measured by enzyme-linked immunosorbent assay (ELISA).Results: Mean FGF-19 levels ranged between 12 and 544 pg/ml with a fasting mean value of 105±81 pg/ml and 118±86 pg/ml in OLTT and OGTT. Mean FGF-21 levels ranged between 4 and 1 393 pg/ml with a fasting mean value of 160±204 pg/ml and 235±288 pg/ml in OLTT and OGTT. There was a significant, positive correlation between FGF-19 and FGF-21 in OLTT (p<0.001, r=0.5) and in OGTT (p=0.011, r=0.4). FGF-21 levels were positively correlated with waist circumference and waist hip-ratio in both cohorts. OGTT had no effect on FGF-19 and FGF-21. In contrast, FGF-19 levels were significantly induced and FGF-21 levels were significantly reduced during OLTT.Conclusions: OLTT is a physiological inductor of FGF-19 and a repressor of FGF-21 in healthy adults. There is a significant and positive correlation between FGF-19 and FGF-21. Dietary lipids specifically and differentially regulate FGF-19 and FGF-21 whereas dietary carbohydrates have no effect. The present data provide the clinical basis for the postulated negative feedback loop between dietary lipids and postprandial inhibition of hepatic lipogenesis.
Keywords: FGF-19; FGF-21; glucose tolerance test; lipid tolerance test